Analisis Pengaruh Pajak Daerah Terhadap Pendapatan Asli Daerah Kabupaten Dan Kota Di Indonesia - Nahak, Maria Regina Novita; Astuti, Titiek Puji; Sugiarti, Sugiarti Sugiarti (Jurnal Bisnis dan Kewirausahaan, 2023)
The purpose of this study is to obtain empirical evidence regarding the effect of hotel taxes, restaurant taxes, entertainment taxes and parking taxes on local revenue of regencies and cities in Indonesia. The population in this study is the financial statements of regencies and cities throughout Indonesia. The sampling technique uses purposive sampling method and obtained 998 samples during 2 years of observation. The source of data uses in this study is secondary data in the form of district and city financial report documents that have been audited by the Supreme Audit Agency (BPK). The results shows that hotel taxes, restaurant taxes, entertainment taxes, and parking taxes has a positive effect on local revenue. This shows that the level of revenue obtained from local taxes can affect local revenue.